The book of saints : a comprehensive biographical dictionary - Watkins, Basil; St. Augustine's Abbey (Ramsgate, England) (London ; Oxford ; New York ; New Delhi ; Sydney : Bloomsbury T & T Clark, an imprint of Bloomsbury Publishing Plc, 2016)
This is a comprehensive biographical dictionary of saints canonised by the Roman Catholic Church. It contains the names of over 10,000 saints, including all modern ones, with significant information about their lives and achievements. Each section begins with an illustration of a particular saint, and the volume includes a list of national martyrs, a bibliography, and a helpful glossary.
Includes bibliographical references.
Keywords: Christian saints -- Biography -- Dictionaries